Effects of Short-Course Oral Corticosteroid Therapy in Early Dengue Infection in Vietnamese Patients: A Randomized, Placebo-Controlled Trial - Simmons, Cameron (2018)
BACKGROUND: Patients with dengue can experience a variety of serious complications including hypovolemic shock, thrombocytopenia, and bleeding. These problems occur as plasma viremia is resolving and are thought to be immunologically mediated. Early corticosteroid therapy may prevent the development of such complications but could also prolong viral clearance. METHODS: We performed a randomized, placebo-controlled, blinded trial of low-dose (0.5 mg/kg) or high-dose (2 mg/kg) oral prednisolone therapy for 3 days in Vietnamese patients aged 5-20 years admitted with dengue and fever for ≤72 hours, aiming to assess potential harms from steroid use during the viremic phase. Intention-to-treat analysis was performed using linear trend tests with a range of clinical and virological endpoints specified in advance. In addition to recognized complications of dengue, we focused on the are under the curve for serial plasma viremia measurements and the number of days after enrollment to negative viremia and dengue nonstructural protein 1 status. RESULTS: Between August 2009 and January 2011, 225 participants were randomized to 1 of the 3 treatment arms. Baseline characteristics were similar across the groups. All patients recovered fully and adverse events were infrequent. Aside from a trend toward hyperglycemia in the steroid recipients, we found no association between treatment allocation and any of the predefined clinical, hematological, or virological endpoints. CONCLUSIONS: Use of oral prednisolone during the early acute phase of dengue infection was not associated with prolongation of viremia or other adverse effects. Although not powered to assess efficacy, we found no reduction in the development of shock or other recognized complications of dengue virus infection in this study.